Parapatric speciation found in limnonectes (Dicroglossidae) species in Thailand - Pimwipa Teerawarunyoo (2018)
© 2017 The Authors. Biodiversity stems from speciation, and species identification allows scientists to measure species biodiversity. However, some closely related species, particularly amphibians that choose to inhabit the same environment, are difficult to identify. Juvenile specimens of Limnonectes gyldenstolpei (Lg) and L. taylori (Lt) were used as models to study the speciation process in populations with a parapatric distribution. Samples of the two species were collected from six provinces in the north and northeast of Thailand. Inter-simple sequence repeat (ISSR) data of five loci showed 96 polymorphic bands and species-specific bands of the primers UBC811 (Lg) and UBC824 (Lt). There was limited genetic variation within the same population, 8% in Lg and 2% in Lt, whereas a high genetic variation was observed between populations from different provinces 90% and 97% in Lg and Lt, respectively. An unweighted pair-group method using arithmetic averages (UPGMA) tree was constructed for each population using Jaccard’s similarity efficient. The tree demonstrated genetic differentiation between the two species. Principal coordinates analysis also supported the UPGMA diagram by showing no clear clusters with close genetic distances. The results of the molecular variance analysis within the population were high, indicating that they were genetically similar, and that microhabitat is an important factor influencing genetic distribution. Overall, the present study proves the hypothesis that the distribution of the two species is in a Parapatric form and that the ISSR technique is inappropriate tool to study the differentiation of a species complex.